“Efecto de la concentración del aceite esencial de Citrus paradisi L. sobre la viabilidad de Candida albicans in vitro” - Corcuera Castillo, Gavi del Rocío (2017)
The present study aimed to study the effect of the concentration of the essential oil of Citrus paradisi "grapefruit" on the viability of Candida albicans and with this to initiate new investigations in order to determine the activity of this fruit, as well as its effects on the treatment of new diseases. For this the fruit of the grapefruit of the bean district was collected, from its shell the essential oil was extracted by steam distillation, then it was placed in vials containing twen 80 to 0,1% in distilled water and the oil of grapefruit at concentrations of 10, 20, 30, 40, 50 and 60 ug/μl respectively. C. albicans was seeded on plates with Sabouraud agar and allowed to dry. In each plate 5 mm diameter holes were aseptically performed in which the concentrations of the above mentioned grapefruit essential oil were added; was incubated at 36 ° C for 24 hours. It was observed that at concentrations below 40 ug / mL there is no formation of halos that affect viability, whereas at concentrations greater than and equal to 40 ug/mL halos are observed affecting the viability of C. albicans (> 20 mm of diameter), it is concluded that at higher and equal concentrations of 40 ug / mL affect the viability of C. albicans in vitro.